Communication, cross talk and signal integration in the adult hippocampal neurogenic niche - Vicidomini, Cinzia (Neuron, 2020)
Radial glia-like neural stem cells (RGLs) in the dentate gyrus subregion of the hippocampus give rise to dentate granule cells (DGCs) and astrocytes throughout life, a process referred to as adult hippocampal neurogenesis. Adult hippocampal neurogenesis is sensitive to experiences suggesting that it may represent an adaptive mechanism by which hippocampal circuitry is modified in response to environmental demands. Experiential information is conveyed to RGLs, progenitors and adult-born DGCs via the neurogenic niche that is comprised of diverse cell-types, extracellular matrix, and afferents. Understanding how the niche performs its functions may guide strategies to maintain its healthspan and provide a permissive milieu for neurogenesis. Here, we first discuss representative contributions of niche-cell types to regulation of NSC homeostasis and maturation of adult-born DGCs. We then consider mechanisms by which the activity of multiple niche cell-types maybe coordinated to communicate signals to NSCs. Finally, we speculate how NSCs integrate niche-derived signals to govern their regulation.